Local Community Participation Beraban Village in The Management of Tanah Lot Tourism Object Kediri District Tabanan Regency, Bali - Dewi, Roels Ni Made Sri Puspa; Priyambodo, Tri Kuntoro; Irwan, Siti Nurul Rofiqo (Stupa, 2019)
The community as the main actor in the management of tourist attractions is very important in tourism development. The role of community can be as a medium to preserve the social cultural values ​​in these attractions. Tanah Lot tourism attraction is one of the biggest tourist attractions in Bali which has a high number of tourist visits. Tanah Lot is managed by two parties, namely the Government of Tabanan Regency and the local community of Beraban Village. The purpose of this study was to measure the stage of community participation in the management of Tanah Lot. Community participation in the management of Tanah Lot attractions in the planning stage, the score is 2.25, the implementation stage is 4.35, the benefit-taking stage is 4.72 and the supervision stage is 4.14. The high level of community participation at the implementation, benefit-taking, supervision and evaluation stages is due to the management of Tanah Lot handed over to the Customary Village (Desa Adat). The lowest stage of community participation in management of Tanah Lot is the planning stage. The low level of community participation at this stage is due to three factors: cooperation agreement, internal factor and external factor of the community.